Calculated characterisation of a sensitive gas sensor based on PEDOT:PSS - Mokhtar Aarabi; Alireza Salehi; Alireza Kashaninia (IET Circuits, Devices and Systems)
Abstract The interactions between poly (3,4‐ethylene dioxythiophene) poly (styrenesulfonate) (PEDOT:PSS) and small gas molecules are studied using non‐equilibrium Green's function formalism based on the density functional theory. The proposed method is implemented in the Tran SIESTA code to benefit from the potential application of PEDOT:PSS as a gas sensor. The results show that doping with nanoparticles can drastically improve the sensitivity of polymer‐based chemical gas sensors. Moreover, among various PEDOT:PSS doping materials, silver nanoparticles have an appropriate response to ammonia, while platinum shows the best response to carbon dioxide. The numerical results can be useful to design PEDOT:PSS‐based gas sensors.